Identification of Structural Features of Hydrocinnamic Acid Related to Its Allelopathic Activity against the Parasitic Weed Cuscuta campestris - Antonio Moreno-Robles; Antonio Cala Peralta; Jesús G. Zorrilla; Gabriele Soriano; Marco Masi; Susana Vilariño-Rodríguez; Alessio Cimmino; Mónica Fernández-Aparicio (Plants, 2022)
Cuscuta campestris is a parasitic weed species that inflicts worldwide noxious effects in many broadleaf crops due to its capacity to withdraw nutrients and water directly from the crop vascular system using haustorial connections. Cuscuta campestris control in the majority of crops affected is non-existent, and thus, research for the development of control methods is needed. Hydrocinnamic acid occurs naturally in the rhizosphere, playing regulatory roles in plant–plant and plant–microbe communities. The toxicity of hydrocinnamic acid against C. campestris was recently identified. In the present work, a structure–activity relationship study of 21 hydrocinnamic acid analogues was performed to identify key structural features needed for its allelopathic action against the seedling growth of this parasitic plant. The findings of this study provide the first step for the design of herbicides with enhanced activity for the control of C. campestris infection.